English Teaching Centered on the Application of Learning Styles Perceived in Academic Contexts - NADHIM ALI (مجلة اداب ذي قار)
This study explores the influence of learning styles and their impact on the student's ‎achievement in the target language. The primary purpose of teaching is to enable students to adopt various learning styles to improve their language skills. Therefore, teachers can use VARK to accommodate their students' diverse learning preferences when teaching English activities in a formal setting. The study has shown the existence of correlation coefficients between English proficiency and learning style preferences, precisely the preparatory students' visual and auditory learning styles, are strongly positive. The Pearson Chi-Square value for the Visual model is c2 =193.37, p<‎0.05, and the Aural model is c2=182.70, p<‎0.05. Besides, it illustrates that out of the total 64 participants, the single preference model accounted for the most significant rating score (M=3.22, SD=.863), comprising 39.1% of the sample. In contrast, the results suggest no statistically significant distinction between male and female participants concerning the reference of gender preference in VARK, p <0.05. Teachers should possess an in-depth understanding of the preferred learning styles of their students to develop teaching resources that facilitate rapid and effective student learning. Furthermore, it seems that both students and teachers readily embrace the notion of learning styles, which enhances the actual use of learning style measurement in classroom settings to identify students' areas of particular difficulty in the learning process.